Volatile Phenols Are Produced by Strains of Dekkera Bruxellensis Under Brazilian Fuel Ethanol Industry-Like Conditions - Ganga-Munoz, M; Peña-Bernales, R (Oxford University Press, 2018)
Dekkera bruxellensis is a spoilage yeast in wine and fuel ethanol fermentations able to produce volatile phenols from hydroxycinnamic acids by the action of the enzymes cinnamate decarboxylase (CD) and vinyphenol reductase (VR) in wine. However, there is no information about this ability in the bioethanol industry. This work evaluated CD and VR activities and 4-ethylphenol production from p-coumaric acid by three strains of D. bruxellensis and PE-2, an industrial Saccharomyces cerevisiae strain. Single and multiple-cycle batch fermentations in molasses and sugarcane juice were carried out. Dekkera bruxellensis strains showed similar CD activity but differences in VR activity. No production of 4-ethylphenol by S. cerevisiae in any fermentation system or media was observed. The concentrations of 4-ethylphenol peaked during active growth of D. bruxellensis in single-cycle fermentation but they were lower than in multiple-cycle fermentation. Higher concentrations were observed in molasses with molar conversion (p-coumaric acid to 4-ethylphenol) ranging from 45% to 85%. As the first report on 4-ethylphenol production in sugarcane musts by D. bruxellensis in industry-like conditions, it opens up a new avenue to investigate its effect on the viability and fermentative capacity of S. cerevisiae as well as to understand the interaction between the yeasts in the bioethanol industry. © FEMS 2018. All rights reserved.